Concept Model Research of Financial Psychology to SME Business Sustainability - Oktariswan, Dony; Manurung, Adler Haymans; Ulupui, I Gusti Ketut Agung; Buchdadi, Agung Dharmawan (International Journal Labs, 2022)
The study of Financial Psychology to SME Business Sustainability is one of the most efficient methods to improve Financial Psychology in doing business. The purpose of this study is to review and analyze the development of article publications with the evolution of research on Financial Psychology to SME Business Sustainability published from 2019-2021. Article analysis and search involves only themes with titles, abstracts, and keywords related to Financial Psychology and SME Business Sustainability from 2019-2021. Searches through the Scpous database are performed using TITLEABS-KEY. Article selection is adjusted by eliminating duplicates in the list of article type documents sourced from journals taken from the database using Harzing's Publish or Perish (PoP) and VOSviewer software. Based on the results of the analysis obtained research concept models in Financial Psychology formed from Financial Planning (Social factors and Economic factors), Behavior Finance (Psychological & Emotional and Factors Situational stimuli), Financial Literacy (Financial Knowledge and Household finance), Financial Inclusion (Government policy & regulation and Bank Stability). While Implementation Accounting from application, and SME Business Sustainability formed from SME Sustainability Performance. The subject area on the concept of the model was obtained from the disciplines of Economic, Econometrics and finance as many as 34 (42.5%) and Business, Management & Accounting amounted to 33 (41.25%).